Hospitality employees' unrealistic optimism in promotion perception: myth or reality?. Issue 2 (3rd April 2019) - Ngan, Henrique Fátima Boyol; Tze-Ngai Vong, Louis
Abstract: The present study examines the degree of optimistic bias in employees towards their career prospect, namely promotion opportunities. By comparing the expected promotion time of hospitality employees and the actual average promotion time of their respective job position, this study revealed that employees at the entry level position are the most optimistically biased towards their promotion expectations. This unrealistic expectation is rooted in infrequent appraisals and performance feedback that is translated into negative work outcomes (i.e. lower intent to stay and job satisfaction). Managerial implications are subsequently discussed.